2020
DOI: 10.1093/jac/dkaa149
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose liposomal amphotericin B for antifungal prophylaxis in paediatric allogeneic haematopoietic stem cell transplantation

Abstract: Background Primary antifungal prophylaxis in paediatric allogeneic HSCT recipients is mainly based on azoles, which can have related toxicity and drug interactions. Low-dose liposomal amphotericin B (L-AmB) is an attractive intravenous alternative because of its low toxicity and lower risk of interactions. Objectives To evaluate the effectiveness and safety of L-AmB (1 mg/kg/day) for primary antifungal prophylaxis in pre-engr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In vivo studies have suggested AMB as an efficacious alternative for patients with infections refractory to echinocandins or those infected with multidrug-resistant isolates (Olson et al, 2005;Binder et al, 2020). Moreover, clinical studies have suggested that LAMB is a safe and efficacious prophylactic option for invasive fungal infections in pediatric patients undergoing hematopoietic stem cell transplantation (Mendoza-Palomar et al, 2020). Systematic reviewing of the literature showed that amphotericin B seems to be the optimal choice for the treatment of W. anomalus infections, and lipid complex amphotericin B could be used in patients with acute renal failure (Goss et al, 1994;Kane et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have suggested AMB as an efficacious alternative for patients with infections refractory to echinocandins or those infected with multidrug-resistant isolates (Olson et al, 2005;Binder et al, 2020). Moreover, clinical studies have suggested that LAMB is a safe and efficacious prophylactic option for invasive fungal infections in pediatric patients undergoing hematopoietic stem cell transplantation (Mendoza-Palomar et al, 2020). Systematic reviewing of the literature showed that amphotericin B seems to be the optimal choice for the treatment of W. anomalus infections, and lipid complex amphotericin B could be used in patients with acute renal failure (Goss et al, 1994;Kane et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the distribution of AF, LAMB was the most prescribed drug in our study, followed by posaconazole. At our hospital, low-dose LAMB is the drug of choice for AF prophylaxis in high-risk cancer patients (relapsed or refractory leukaemia, HSCT preengraftment phase) due to its effectiveness and safety profile as shown in a previous paper by our group [16]. LAMB is also used in critically ill paediatric patients due to its stability with the concomitant use of continuous renal replacement therapy, as opposed to azole elimination [17].…”
Section: Clinical Situation Amentioning
confidence: 94%
“…Seven studies reported CMV definitions according to the standard definitions and were included in the subgroup analyses. 29,31,33,39,40,42 Both CMV disease and CMV viremia increased the risk of subsequent IFI with pHR of 6.03 (4.04, 9.00), p-value < 0.001, I 2 = 42% and 3.58 (1.75, 7.35), p-value < 0.001, I 2 = 38%, respectively (Figure 3 and S5). Both unadjusted and adjusted effect estimates of CMV increased the risk of subsequent IFIs with pHRs of 1.70 (1.14, 2.55), p = 0.009, I 2 = 14% and 2.99 (1.92, 4.67), p < 0.001, I 2 = 76%, respectively (Figure 3…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A total of 18 studies were extracted for the systematic review. 16,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Six articles were excluded from meta-analysis due to lack of HR. 32,34,36,38,41,45 Accordingly, 12 studies were included for meta-analysis of post-transplant CMV and IFIs.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%